Tela’ah Aspek Lokalitas Kitab Tafsir Pathok Nagari Karya Aliy As’ad - Khamidatul Laila; Muhammad Zaini; Muhammad Ridho; Fadila Ikke Nuralita; Rosyida Amalia (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This researchfocuses on the interpretive work of Indonesian cleric Aliy As’ad under the name Tafsir Pathok Nagari. the name of the tafsir is taken from the name of the mosque where this book is used as a medium for routine recitation of the people of the Yogyakarta area. This research is analyzing the locality aspect in Pathok Nagari tafsir of the Qur’an using vernacular theory which consists of three aspects of locality in the Pathok Nagari tafsir: (1) Locality in terms of language, this tafsir uses Jjavanese and Indonesian in translating verses. The use of Javanese in the interpretation shows the identity of the people of Yogyakarta who use this language in their daily lives. (2) Locality from social and cultural aspects, namely the reason Aliy As’ad wrote his book of tafsir was for the media of preaching which was held regularly at the Pathok Nagara mosque. (3) Locality in terms of interpretation, in this chapter Aliy As’ad interprets QS. Al-Fatihah verse 2 takes into account the values or culture of the people of Yogyakarta which is usually called “Sangkan Paraning Dumadi” everything comes from Allah swt and will return to Allah swt. The word “حَمْدٌ” is interpreted as “praise” and is interpreted so that humans raise only Allah Ta'ala. Keywords: Locality, interpretation, Pathok Nagari